PERKEMBANGAN PEREKONOMIAN MASYARAKAT BUGIS DI KELURAHAN MOLAWE KECAMATAN MOLAWE KABUPATEN KONAWE UTARA: 1964-2016 - Arista Mahyudin; Syahrun, Suharni Sudin (Jurusan Ilmu Sejarah Fakultas Ilmu Budaya Universitas Halu Oleo, 2019)
This study discussed the migration of Bugis Community at Molawe Village. The migration was caused by political turmoil in its native region, Bone. After arriving in Molawe, the Bugis community struggled to survive and survive through several phases. The problems examined in this study were: (1) what were the characterictics of the Bugis community in the economy of Molawe Village, (2) what factors which support the development of the economic life of the Bugis community in Molawe Village. The method used in this study was the historical method with the following stages: 1) Topic selection, 2) Collection of sources), 3) Source criticism (external and internal), 4) Interpretation of sources (analysis and synthesis), 5) Historiography. The results showed that: 1) the characteristics of Bugis community in the economy at the Molawe Village were divided into two periods, namely 1964-1990 and 1990-2016.In those two periods there were significant differences in the economy of the Bugis community at Molawe, where in the period of 1964-1990 the Bugis lived with simple knowledge and skills so that their production was limited to their daily need. While the 1990-2016 period, the Bugis community had begun to use modern infrastucture in fishing and farming so that their economic income increases. 2) the economic life of the Bugis community at Molawe Village was supported by various factors such as geographic location and condition, the availability of human resources, the potential of natural resources, and the development of science and technology. Keyword: Bugis Community, Development, Economic Factors